ANALISIS PENILAIAN NASABAH TERHADAP KINERJA MARKETING PADA PT BANK MUAMALAT INDONESIA - Ulen, Bangun; Rizky, Fatmawati; Rusda , Hayati (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2022)
The purpose of this study is to determine the criteria for customer assessment of marketing performance and to see whether the customer assessment can improve marketing performance. The method used in this research is descriptive. Based on the results of the research, the assessment carried out by the bank is seen from how the employee works, discipline, and responsibility for his work. Assessment can also be done by customers, in the form of criticism or suggestions. These two things will be evaluated later. A good assessment will have an impact on the enthusiasm of the employees to continue to provide good performance, namely in the form of appreciation, rewards and so on. Vice versa, a bad assessment will have a bad impact on employee.